PAVEMENT ROAD DESIGN OF CIKEBO MAJALENGKA - Ingrid Multi Rezeki; Dede Rukmawati (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2021)
The condition of construction of a good pavement is sought to be able to meet the functional requirements of providing a sense of security and comfort as well as the minimum time and distance for road users. Therefore, it is deemed necessary to build a new road infrastructure alternative roads to avoid congestion from markets and terminals, in order to provide security and comfort for road users, as well as a more efficient travel time. In making this final assignment the author wants to plan the geometric path that is in accordance with the function and class of the road, safe to pass and accelerate travel time, and plan the thickness of the pavement.  planned type of pavement is rigid pavement with an estimated design life of 20 years, Traffic growth rates (i) 5%, road plan local road class, heaviest axle load 8 Ton (UU No.22 Th. 2009), value plan CBR 6% (from PUPR), Rainfall 4362 mm/year (2019), Pavement type plan rigid pavement reinforcement without continued, and the thickness of pavement obtained from the calculation is 15 cm for the surface layer.